REVIEW: EFFICIENT DEEP PACKET INSPECTIONALGORITHMS FOR INTRUSION DETECTIONSYSTEMS - Nauruzbayeva, Farikha; Imankulova, Assemay; Seitkaliyeva, Gaukhar; Manbay, Shakhnazar-Sultan (Journal of Emerging Technologies and Computing, 2024)
This study explores the field of intrusion detection systems(IDS) and network security, with a special emphasis on the role that deep packet inspection (DPI) techniques play in protecting computer networks from a variety of online threats. Intentional intrusions into computer networks, or network attacks, can have criminal undertones. The attacker may want to take over the system, obtain sensitive data, interfere with network functions, or even takedown websites and servers. The growing frequency of attacks on ITinfrastructure highlights the need of intrusion detection, as per the report. It points to a gap in the body of knowledge about how well DPI algorithms work to counter vulnerabilities. The analysis highlights how bad network security is right now, including startling data on ransomware assaults, cyberattacks that target small organizations, and data breaches that cause significant financiallosses. According to the report, human error is still a major weakness in network security. Intrusion detection systems (IDS) are frequently used to prevent unwanted access and safeguard systems. IDS entails identifying and evaluating system or network events in order to spot possible intrusions and stop malicious activity. Network security is emphasized as a major concern since malicious actors are constantly coming up with new ways to attack networks. This study’s main goal is to investigate and compile the body of knowledge regarding different DPI intrusion detection techniques. It suggests creating a morphological framework for IDS in order to help us comprehendthese systems on a deeper level. The study provides a thorough explanation of the various DPI kinds and the algorithms that go along with them.